Montréal, haut lieu de la diplomatie autochtone - Arsenault, Mathieu (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Autochtones; Parlement

Montréal, Heart of Indigenous Diplomacy - Arsenault, Mathieu (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Keywords: Autochtones; Parlement

Le Montréal juif – (3e partie) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2022)
Keywords: Juifs

Le Montréal juif – (2e partie) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2021)
Keywords: Juifs

Le Montréal juif – (4e partie et fin) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2022)
Keywords: Juifs

Histoire des communautés noires au Québec et à Montréal (1ère partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Esclaves; Noirs

Histoire des communautés noires au Québec et à Montréal (3e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Haïtiens; Noirs

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Chemins de fer; Musique; Noirs; Travail

Le High School of Montreal: fer de lance de l'enseignement anglo-protestant - MacLeod, Roderick; Poutanen, Mary Anne (Atlas historique du Québec. L'école au Québec, 2023)
Keywords: Anglophones; High School of Montreal; Protestants

« Des mots et des commandements déplacés ». La prise en charge des étudiants vietnamiens du Plan Colombo à l’Université de Montréal (1950–1959) - Poitras, Daniel (Historical Studies in Education / Revue d'histoire de l'éducation, 2023)
Keywords: Université de Montréal; Vietnamiens; Étudiants

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

Antijudaïsme et influence nazie au Québec. Le cas du journal L'Action catholique de Québec: 1931-1939 - Anctil, Pierre (PUM, 2021)
"Comment les francophones du Québec ont-ils réagi au début du XXe siècle aux premières manifestations de la diversité culturelle? Ce livre explore l'accueil fait à l'immigration irlandaise, juive est-européenne et chinoise au cours des années 1930 à Québec, tel que vu à travers le prisme du journal L'Action catholique. Il explore en particulier la réaction à l'apparition de commerces juifs dans la capitale provinciale, et en particulier à l'ouverture en 1931 du grand magasin tenu par Maurice Pollack."--
Keywords: Action catholique; Idéologies; Juifs

Mainmise sur la contre-culture américaine: la traduction comme véhicule de transfert culturel - Ruschiensky, Carmen (Relire les revues québécoises: histoire, formes et pratiques (XXe-XXIe siècle), 2021)
Keywords: Traduction

« Glad of your help »: Scottish Architects in Montreal, 1860-1940 - Adams, Annmarie (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Golden Square Mile; Royal Victoria Hospital; Écossais

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Routes; Saint-Laurent (rue)

Le boulevard Saint-Laurent et son histoire-(suite 1) - Tessier, Stéphane (Il était un fois... Montréal Nord, 2023)
Keywords: Juifs; Saint-Laurent (rue)

Le boulevard Saint-Laurent et son histoire-(suite 2) - Tessier, Stéphane (Il était un fois... Montréal Nord, 2023)
Keywords: Chinois; Juifs; Saint-Laurent (rue)

Jackie Robinson...Un Américain à Villeray - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2024)
Keywords: Baseball; Noirs; Villeray

Where They Stood: The Evolution of the Black Anglo Community in Montreal (Linda Leith Publlishing, 2023)
Keywords: Anglophones; Noirs

Il fallait se défendre: l'histoire du premier gang de rue haïtien à Montréal - Aurélien, Maxime; Rutland, Ted (Mémoire d'encrier, 2023)
Keywords: Criminalité; Délinquance; Haïtiens; Noirs

One long line of marvel: 200 years of Montreal's St. Patrick's parade - Hustak, Alan (Véhicule press, 2024)
Keywords: Irlandais; Processions

Una gatta da pelare : vies publiques et vies privées des Italiennes récemment arrivées à Montréal - Vigliano, Chiara (Université de Montréal, 2021)
Keywords: Femmes; Italiens

Les Irlandais catholiques de Montréal : genèse d'une communauté, 1800-1834 - Duchesne, Jonathan (Université du Québec à Montréal, 2021)
Keywords: Famille; Irlandais; Mariage

Parcours migratoires et re-constructions identitaires de femmes d'ascendance maghrébine à Montréal - Boukerrou, Yasmine (Université du Québec à Montréal, 2022)
Keywords: Femmes; Maghrébins

Le Québec anglophone: une communauté distincte du reste du Canada? : étude comparative des positions éditoriales de deux journaux anglophones - The Gazette et The Globe and Mail - en rapport avec certains débats publics au Québec et au Canada de 1976 à 1982 - Lacasse, Chantal (Université Laval, 2022)
Keywords: Anglophones; Francophones; Fédéralisme; Indépendantisme; Montreal Gazette; Nationalisme

« Dear Richard...send us a few buffalo tongue »: Donald Smith's Fur Trade Contacts and Peronal Credit Networks - Hamon, Max (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Autochtones; Bourgeoisie; Chemins de fer; Femmes; Fourrure; Golden Square Mile

Le vice et la vertu: le Montréal 1940-1960 - Weintraub, William (Éditions Pierre Tisseyre, 2020)

Du Centro Donne Italiane di Montréal aux Donne d’Acciaio. - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2023)
Keywords: Ahuntsic; Femmes; Féminisme; Italiens

George M. Brewer et le milieu culturel anglophone montréalais, 1900-1950 - Huston, Lorne; Lefebvre, Marie-Thérèse (Septentrion, 2020)
Keywords: Anglophones; Francophones; Musicien; Musique; Théâtre

Civic Identities in Conflict: Montreal's Anglophone and Francophone Private School Girls - Moore, Lisa (Making the Best of It. Women and Girls of Canada and Newfoundland during the Second World War, 2020)
Keywords: Anglophones; Francophones; Étudiants

L’intimité française avec la " sauvagerie " à Montréal aux 17e-18e siècles - Deslandres, Dominique (Dix-huitième siècle, 2020)
Keywords: Autochtones; Criminalité; Délinquance; Français

Dal Mediterraneo all’Atlantico: ricordi di migrazione nella Montréal del secondo dopoguerra - Piraro, Sergio (Italian Canadiana, 2021)
Keywords: Italiens

Idealized Spaces, Internationalized Selves: Japanese Migration to Montreal, Canada, 1990-Present - Tabakow, Elizabeth (Université Concordia, 2021)
Keywords: Japonais

A Fractured Identity: The 1980 Referendum and the Italians of Montreal - Pannunzio, Anthony (Université McGill, 2022)
Keywords: Indépendantisme; Italiens; Nationalisme; Référendums

Divvying up Space: Housing Segregation and National Identity in Early Twentieth-Century Montréal - Sweeny, Robert C. H. (Sharing Spaces: Essays in Honour of Sherry Olson, 2020)
Keywords: Locataires; Logement; Quartiers

The harp and the shamrock: the two faces of Montreal's Irish community - Bâby, Françoise (The Westmount Historian, 2023)
Keywords: Griffintown; Irlandais

“A Curse or a Blessing?”: Montreal Jews and the Politics of 1960s Quebec - Lacasse, Simon-Pierre (Canadian Historical Review, 2022)
Keywords: Juifs; Nationalisme

By the Rivers of the St Lawrence: The Montreal Jewish Community and Its Postmemory - Robinson, Ira (No better home? Jews, Canada, and the Sense of Belonging, 2021)
Keywords: Juifs

Vilna on the St Lawrence: Montreal as the Would-Be Haven for Yiddish Culture - Weiser, Kalman (No better home? Jews, Canada, and the Sense of Belonging, 2021)
Keywords: Juifs

“The Most Distinctively Canadian City” Representations of the City in Montreal Guidebooks, 1876–1892 - Lamoureux, François (Urban History Review/Revue d'histoire urbaine, 2023)
Keywords: Anglophones; Métropole; Tourisme

Elites and Scottishness in Montreal: identity, culture and the self in portait photography, 1860-1900 - Regimbald-Roy, Florence (Université McGill, 2021)
Keywords: Notman, William; Photographie; Écossais

Negotiating Bella Figura: Inside the Childhood Homes of Six Second-Generation Italian-Canadian Women in Montreal - Massa, Lisa (Université Concordia, 2022)
Keywords: Enfants; Femmes; Italiens

Tim Tim? Bwa Chèch! : Documentation de la présence des artistes visuels haïtiens à Montréal 1971-1986 - Theliar-Charles, Kessie (Université Concordia, 2023)
Keywords: Haïtiens

La Maison d’Haïti: Haitian Stories of Resistance and Black Diasporic Activism in Montréal, 1972–1986 - Rochat, Désirée (Histoire sociale / Social History, 2022)
Keywords: Haïtiens; Noirs

British Philanthropists and the Imperial Imagination or The Case of the Canadians Distressed by Fire at Montreal - Eamon, Michael (Canadian Historical Review, 2020)
Keywords: Britanniques; Incendies; Philanthropie

Roman familial, roman national? L'histoire de Montréal sous la loupe de la filiation généalogique féminine (Première partie) - Deslandres, Dominique (Les Cahiers des Dix, 2020)
Keywords: Autochtones; Famille; Femmes; Français; Mariage

Trouble at the Edge of Town: Policing Montreal’s Urban Periphery in the Middle of the Nineteenth Century - Horner, Dan (Micro-Geographies of the Western City, c.1750-1900, 2020)
Keywords: Irlandais; Lachine (canal); Police

“The People Who Stayed”: Back River Memorial Gardens Cemetery as a Site of Jewish Migrant and Montreal Urban Meaning-Making - Frost, Naomi; Sheftel, Anna (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Ahuntsic; Cimetières; Juifs

Dos blaybt tsu zen : le journal yiddish de Montréal, Der Keneder Odler, Maurice Duplessis et le Québec, 1936-37. - Victor, Sacha (Université d'Ottawa, 2023)
Keywords: Juifs

Du pragmatisme à l’engagement. Les militants chiliens à Montréal et leurs relations avec le milieu politique local : influences et interactions réciproques - Del Pozo, José (Bulletin d'histoire politique, 2023)
Keywords: Chiliens

Les " jeunes ", les " amazones ", les " célestes ": les figures de la panique morale sur les drogues à Montréal dans le journal La Patrie, entre 1921 et 1923 - Grenier, Amélie (Bulletin d'histoire politique, 2020)
Keywords: Chinois; Criminalité; Femmes; Patrie (La); Réformistes

Hair 1970. La tribu métissée du Québec - Lavertu, Yves (Éditions Yves Lavertu, 2020)
Keywords: Musique; Noirs; Théâtre

Red mitten nationalism: sport, commercialism, and settler colonialism in Canada - Fresco, Estée (McGill-Queen's University Press, 2022)
Keywords: Autochtones; Jeux olympiques; Nationalisme

Redéfinir le Canada et le Québec : les représentations identitaires du Centenaire de la Confédération et de l'Expo 67 chez les journalistes - Blais, Caroline (Université du Québec à Montréal, 2021)
Keywords: Anglophones; Expositions; Francophones; Journalistes

Montréalaises d'origine haïtienne : communauté d'entraide et luttes féministes de 1970 à 1995 - Bélanger, Jasmine (Université du Québec à Montréal, 2020)
Keywords: Femmes; Féminisme; Haïtiens

Statesman of the Piano: Jazz, Race, and History in the life of Lou Hooper - Mills, Sean; Fillion, Eric; Rochat, Désirée (McGill-Queen's University Press, 2023)
Keywords: Musique